2022
DOI: 10.1016/j.neuroimage.2021.118800
|View full text |Cite
|
Sign up to set email alerts
|

Classification of emotion categories based on functional connectivity patterns of the human brain

Abstract: Neurophysiological and psychological models posit that emotions depend on connections across wide-spread corticolimbic circuits. While previous studies using pattern recognition on neuroimaging data have shown differences between various discrete emotions in brain activity patterns, less is known about the differences in functional connectivity. Thus, we employed multivariate pattern analysis on functional magnetic resonance imaging data (i) to develop a pipeline for applying pattern recognition in functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 101 publications
2
27
0
Order By: Relevance
“…Although these studies demonstrated the feasibility to decode specific emotions from FC patterns, the performance varied between emotional categories, in particular the specificity and accuracy for sadness remained limited. For instance, despite a high accuracy obtained for most emotions in Saarimä ki et al's study (Saarimä ki et al, 2022), it revealed a classification accuracy of sadness was close to chance level (18% accuracy). One possible reason might be the different time frames of emotional experiences and thus the difficulty in robustly evoking strong and engaging feelings of sadness with experimental stimuli as short as one minute.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Although these studies demonstrated the feasibility to decode specific emotions from FC patterns, the performance varied between emotional categories, in particular the specificity and accuracy for sadness remained limited. For instance, despite a high accuracy obtained for most emotions in Saarimä ki et al's study (Saarimä ki et al, 2022), it revealed a classification accuracy of sadness was close to chance level (18% accuracy). One possible reason might be the different time frames of emotional experiences and thus the difficulty in robustly evoking strong and engaging feelings of sadness with experimental stimuli as short as one minute.…”
Section: Introductionmentioning
confidence: 69%
“…For example, in Saarimä ki et al's work(Saarimä ki et al, 2022), the mean classification accuracy on sadness was the lowest (18%), which was close to the chance level (16.67%). A similar situation occurred in another fMRI-based emotion recognition work(Saarimä ki et al, 2016), where the emotion prediction result on sadness was still the lowest.…”
mentioning
confidence: 72%
See 3 more Smart Citations